Chronic toxicity of heavy fuel oils to fish embryos using multiple exposure scenarios. (24th January 2014) - Martin, Jonathan D.; Adams, Julie; Hollebone, Bruce; King, Thomas; Brown, R. Stephen; Hodson, Peter V.
Abstract The chronic toxicity to rainbow trout (Oncorhynchus mykiss) embryos of heavy fuel oil (HFO) 6303, weathered HFO 6303, HFO 7102, and medium South American (MESA) crude oil was assessed by different exposure regimes. These included water accommodated fractions (WAF; water in contact with floating oil), chemically enhanced WAF (CEWAF; oil dispersed with Corexit 9500), and effluent from columns of gravel coated with stranded oil. Heavy fuel oil WAF was nontoxic and did not contain detectable concentrations of hydrocarbons, likely because the high density and viscosity of HFO prevented droplet formation. In contrast, chemically dispersed HFO and effluent from columns of stranded HFO contained measurable concentrations of alkyl polycyclic aromatic hydrocarbons (PAH), coincident with embryo toxicity. These exposure regimes enhanced the surface area of oil in contact with water, facilitating oil–water partitioning of hydrocarbons. Heavy fuel oil was consistently more toxic to fish than crude oil and the rank order of alkyl PAH concentrations in whole oil were sufficient to explain the rank order of toxicity, regardless of exposure method. Thus, the propensity of HFO to sink and strand in spawning shoals creates a long‐term risk to developing fish because of the sustained release of PAHs from HFO to interstitial waters. Further, PAH monitoring is key to accurate risk assessment. Environ Toxicol Chem 2014;33:677–687. © 2013 SETAC